Sensitization and Assessment of Knowledge of Ayurveda Panchakarma Therapy Among ASHA Workers in Wardha Taluka: Life Science-Ayurveda - Chaple, Dr. Jagruti; Sawarkar, Dr. Punam; S. Rajput, Dr. Dhirajsingh (International Journal of Life Science and Pharma Research, 2023)
A village-level community health worker, an "Accredited Social Health Activist " (ASHA), bridges community and healthcare facilities. The ASHA workers act as catalysts in promoting various foundation programs and encourage people to avail the available benefits. The study aimed to assess knowledge of Panchakarma in ASHA Workers & Sensitization with the Panchakarma module in Wardha taluka. The study's objectives include designing a Panchakarma questionnaire module to assess the knowledge and awareness of ASHA workers of Wardha Taluka and sensitizing ASHA workers about Panchakarma procedures with the help of demonstration videos and lectures on Panchakarma. The work was planned to be conducted at Anji and Waifad villages under Wardha taluka. A questionnaire consisting of 30 questions was prepared to assess the knowledge, awareness, and attitudes regarding Panchakarma. Panchakarma's knowledge, awareness, and attitudes were analyzed using pre-and post-test scores. ASHA will be a facilitator for promoting awareness in the community about Panchakarma. The study concluded that the intervention of the Panchakarma module was highly influential in enhancing knowledge about Panchakarma among ASHA workers. In the future, this Panchakarma module will enable people in the community to accept the Panchakarma therapy in Ayurveda. ASHA will provide more referral services of panchakarma therapy to patients by encouraging them to undergo these therapies. It was the first footstep in developing the module on awareness regarding Panchakarma therapy to enrich the knowledge of ASHA workers as per their needs and implementation of this module by the ASHA in the community.